Обґрунтування напрямів підвищення ефективності економічної діяльності лісових господарств. - Ksjondz, Sergiy; Підгірна, Віра; Сеньовська, Яна (My University, 2019)
Важливим стратегічним завданням на етапі розвитку підприємства будь-якої галузі є досягнення належного рівня його господарської ефективності як основи конкурентоспроможності на сучасному ринку. Основне місце у реалі зації цього завдання займає оцінка ефективності господарської діяльності підприємств. Рівень ефективності функ ціонування лісових господарств безпосередньо впливає на розвиток економіки регіону і держави в цілому, стан сус пільного здоров'я населення, а також формування рекреаційної індустрії. Оскільки лісова галузь України розви вається нестабільно, проблема ефективності лісогосподарської діяльності поступово набула актуального значення. Проблеми охорони навколишнього середовища та погіршення екологічного стану територій зумовлює створен ня ефективного механізму ведення лісогосподарської діяльності. Таким чином, у статті окреслено оцінку ефектив ності діяльності лісового господарства, а також обгрунтування шляхів її підвищення з врахуванням цільової необхідності використання лісів, посилення їх екологічноBекономічних функцій та дотриманням концепцій сталого розвитку. Тому в статті досліджено сучасний стан розвитку та основні засади ефективності діяльності лісогосподарських підприємств. Виділено основні проблеми та запропоновано напрями підвищення ефективності економічної діяль ності лісогосподарського сектору з їх обгрунтуванням.
An important strategic goal at the stage of enterprise development of any industry is to achieve the proper level of its economic efficiency as a basis for competitiveness in the modern market. One of the main places in the implementation of this task is the evaluation of the efficiency of economic activity of enterprises. The level of forestry efficiency directly influences the development of the economy of the region and the state as a whole, the state of public health of the population, as well as the formation of the recreational industry. As Ukraine's forest industry is developing unstable, the problem of forestry efficiency is urgent. Adaptation to market conditions is accompanied by aggravation of environmental problems and deterioration of the ecological status of territories. This leads to the creation of an effective mechanism for forest activity. Therefore, assessing the effectiveness of forestry operations, as well as justifying ways to increase them, taking into account the targeted need to use forests, enhance their environmental and economic functions, and adhere to sustainable development concepts is important. The issues of finding and justifying directions for improving the efficiency of forestry business with the determinants of external and internal environmental factors, as well as ensuring their sustainable development with the use of new approaches to the activities need further study. The use of innovative methods of forestry is an urgent task of enterprises, the efficiency of which depends on the economic efficiency of their activity and development of the country. The main results of our research are: identified the main problems that hinder the development of national forestry enterprises; the factors influencing their sustainable development are identified and analyzed; the strategy of actions which basis for increase of efficiency of activity of forestry is grounded. Therefore, the current state of development and the basic principles of the effectiveness of forestry enterprises was investigated. The main problems are outlined and directions for increasing the efficiency of economic activity of the forestry sector with their justification are proposed.
Keywords: ефективність лісового господарства; стратегічний потенціал,; омплекс6 на стратегія розвитку,; стратегічний аналіз; збалансована система показників; економічна ефективність; orestry efficiency,; trategic potential; ntegrated development strategy; strategic analysis; balanced scorecard; economic efficiency